How do you solve 5-3x=7(x-1)? Algebra 1 Answer Jaime Mar 7, 2018 x=1.2 Explanation: 5-3x=7(x-1) Distribute and multiply the 7 to x and -1 so you get 5-3x=7x-7 Add 7 to -7 and 5 to get 12-3x=7x Add 3x to -3x and 7x to get 12=10x Divide 10 on both sides to get 1.2=x Answer link Related questions How do I determine the molecular shape of a molecule? What is the lewis structure for co2? What is the lewis structure for hcn? How is vsepr used to classify molecules? What are the units used for the ideal gas law? How does Charle's law relate to breathing? What is the ideal gas law constant? How do you calculate the ideal gas law constant? How do you find density in the ideal gas law? Does ideal gas law apply to liquids? Impact of this question 1658 views around the world You can reuse this answer Creative Commons License